The Relationship between Entrepreneurial Education and Entrepreneurial Self-Efficacy toward Entrepreneurial Intention among UTHM Students - Tai Qi Ying,; Juzaimi Nasuredin, (Research in Management of Technology and Business, 2024)
This study explores the intricate relationship between entrepreneurial education, self-efficacy, and entrepreneurial intention among Universiti Tun Hussein Onn Malaysia (UTHM) undergraduate students. Recognizing the pivotal role of entrepreneurial intention in fostering an entrepreneurial environment and stimulating economic growth, the research delves into the multifaceted nature of entrepreneurial intention among Malaysian university students, with conflicting findings on the impact of entrepreneurial education on this aspect. Focusing specifically on UTHM students, the study employs the Theory of Planned Behavior (TPB) framework, utilizing entrepreneurial education and entrepreneurial self-efficacy as key variables to measure factors influencing entrepreneurial intention. By distributing 375 online questionnaires to UTHM undergraduate students and faculty on the main campus, the study collects and analyzes data using SPSS Statistics version 27 software. The findings reveal a positive and significant correlation between entrepreneurial education, entrepreneurial self-efficacy, and entrepreneurial intention, as evidenced by Spearman's rho correlation test. Despite the study's achievements, limitations such as time constraints and a relatively small sample size are acknowledged. Consequently, the research recommends extending the duration and broadening demographic segments to enhance the robustness and generalizability of the findings. This investigation contributes to the understanding of entrepreneurial intention in higher education, emphasizing the need for tailored educational approaches to cultivate a more conducive entrepreneurial environment among UTHM students.